Adult-Diagnosed Nonsyndromic Nephronophthisis in Australian Families Caused by Biallelic NPHP4 Variants - Hudson, Rebecca; Patel, Chirag; Hawley, Carmel M.; O’Shea, Stacey; Snelling, Paul; Ho, Gladys; Holman, Katherine; Bennetts, Bruce; Crawford, Joanna; Francis, Leo; Simons, Cas; Mallett, Andrew (American journal of kidney diseases, 2020)
There is increasing appreciation of nephronophthisis (NPHP) as an autosomal recessive cause of kidney failure and earlier stages of chronic kidney disease among adults. We identified 2 families with presumed adult-diagnosed nonsyndromic NPHP and negative diagnostic genetic testing results from our Renal Genetics Clinic. Both had 2 affected siblings without extrarenal phenotypes. After informed consent, research whole-genome sequencing was undertaken. Biallelic NPHP4 variants were identified in trans and clinically confirmed in all 4 affected individuals, confirming a genetic diagnosis. Participant 1 of the first family (F1P1) had kidney failure diagnosed at 19 years of age. An affected younger sibling (F1P2) reached kidney failure at age 15 years after kidney biopsy suggested NPHP. Pathogenic variants detected in NPHP4 in this family were NM_015102.4:c.3766C>T (p.Gln1256*) and a 31-kb deletion affecting exons 12 to 16. In the second family, F2P3 reached kidney failure at age 27 years having undergone kidney biopsy suggesting NPHP. An affected younger sibling (F2P4) has chronic kidney disease stage 4 at age 39 years. The NPHP4 variants detected were NM_015102.4:c.1998_1999del (p.Tyr667Phefs*23) and c.3646G>T (p.Asp1216Tyr). The latter variant was initially missed in diagnostic sequencing due to inadequate NPHP4 coverage (94.3% exonic coverage). With these reports, we identify NPHP4 as an appreciable genetic cause for adult-diagnosed nonsyndromic NPHP that should be considered by adult nephrologists.